1998
DOI: 10.1111/j.1439-0523.1998.tb01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of five physiological races of blackspot, Diplocarpon rosae, Wolf on roses

Abstract: Differentiation into physiological races of Diplocarpon rosae, which causes blackspot on wild and cultivated roses, was investigated with single conidial isolates of the pathogen. Infection experiments with a simple excised leaf assay demonstrated differential interactions between single isolates and a set of 10 test rose genotypes. Differential reactions could be observed among rose varieties as well as between and within a wild rose species. Accordingly, five different physiological races can be identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 14 publications
3
60
0
Order By: Relevance
“…During our current research, considerable difference in pathogenic potential was observed between the 120 D. rosae isolates tested, with D. rosae DR19 proving to be the most aggressive. Our findings are similar to the results revealed by Debener et al [21] who observed different physiological races of this pathogen. Gachomo [27] also observed variation in virulence of different isolates of D. rosae.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…During our current research, considerable difference in pathogenic potential was observed between the 120 D. rosae isolates tested, with D. rosae DR19 proving to be the most aggressive. Our findings are similar to the results revealed by Debener et al [21] who observed different physiological races of this pathogen. Gachomo [27] also observed variation in virulence of different isolates of D. rosae.…”
Section: Discussionsupporting
confidence: 82%
“…Since, leaves of rose plants raised in glasshouses present in the temperate zones may be kept dry; therefore these plants are not severely infected by black spot disease [13,19]. Different pathotypes of D. rosae have been illustrated using polyconidial [20] and monoconidial [21,22] isolates. Furthermore, different morphotypes have also been observed [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungi were A. alternata, A. flavus, C. cladosporioides, C. oxysporum, C. brachyspora, C. pallescens, M. rosea (Willium 1949, Debner et al 1988, Wikipedia 2013. The spots are circular with a perforated edge and reach a diameter of about 14 mm, badly affected plants however, will not show the circular spots as they combine to cause black mass.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas black spot is considered to be the most severe disease of field-grown roses (Horst 1983;Debener et al 1998;Malek von and Debener 1998;Yokoya et al 2000), powdery mildew is the major fungal pathogen of roses grown in greenhouses (Horst 1983;Linde and Shishkoff 2003). There have been many reports on the development, epidemiology and host -parasite relationship of P. pannosa in which the environmental and cytochemical aspects of the infection process and the defence reaction of the rose were described.…”
Section: Introductionmentioning
confidence: 98%